Nonlinear Dynamic Analysis and Chaos Prediction of Grinding Motorized Spindle System - Weitao Jia; Feng Gao; Yan Li; Wenwu Wu; Zhongwei Li (Shock and Vibration)
The paper determines the impact factors of dynamics of a motorized spindle rotor system due to high speed: centrifugal force and bearing stiffness softening. A nonlinear dynamic model of the grinding motorized spindle system considering the above impact factors is constructed. Through system simulation including phase portraits and Poincaré map, the periodic behavior and chaotic behavior of the nonlinear grinding motorized spindle system are revealed. The threshold curve of chaos motion is obtained through the Melnikov method. The conclusion can provide a theoretical basis for researching deeply the dynamic behaviors of the grinding motorized spindle system.